Changes in kelp forest biomass and depth distribution in Kongsfjorden, Svalbard, between 1996–1998 and 2012–2014 reflect Arctic warming - Bartsch, Inka; Paar, Martin; Fredriksen, Stein; Schwanitz, Max; Daniel, Claudia; Hop, Haakon; Wiencke, Christian (Polar biology, 2016)
Arctic West Spitsbergen in Svalbard is currently experiencing gradual warming due to climate change showing decreased landfast sea-ice and increased sedimentation. In order to document possible changes in 2012–2014, we partially repeated a quantitative diving study from 1996 to 1998 in the kelp forest at Hansneset, Kongsfjorden, along a depth gradient between 0 and 15 m. The seaweed biomass increased between 1996/1998 and 2012/2013 with peak in kelp biomass shifted to shallower depth, from 5 to 2.5 m. The kelp biomass at 2.5 m was 8.2-fold higher in 2012/2013 (14 kg fresh biomass m −2 ) than in 1996/1998 and mostly due to an increase in the kelp Laminaria digitata . This resulted in a very high density of 2- to 8-year-old kelp (70 ind. m −2 ) and a high leaf area index of nearly 10 at 2.5 m. The entire zonation seemed to have shifted upwards to shallower depth, since also the lower depth limit of most dominant brown algae was shallower as well as the biomass maximum of several taxa. The cumulated annual photosynthetic active radiation at 15 m depth (42 mol m −2 year −1 ) determined the current depth limit of kelps. Changes also resulted in an altered seaweed community pattern. The complex pattern of change was probably driven by opposing effects of co-acting environmental drivers, namely lack of ice-scouring, elongation of the open-water period and deterioration of the underwater irradiance climate. The results are interpreted as a consequence of Arctic warming probably reflecting a typical scenario for change along other Arctic shores in near future.